On Halldén Completeness of Modal Logics Determined by Homogeneous Kripke Frames - Kostrzycka, Zofia (Bulletin of the Section of Logic, 2015)
Halldén complete modal logics are defined semantically. They have a nice characterization as they are determined by homogeneous Kripke frames.